Nilai-Nilai Pendidikan Menurut Al-Quran Surat An-Nisa Ayat 58 tentang Kompetensi Guru - Muhammad Qais Arrasyid; Erhamwilda; Fitroh Hayati (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. A professional teacher must have several competencies needed by a teacher. Competence is a form of work that is responsible for achieving a goal. These competencies include Pedagogic competencies, Professional competencies, personality competencies, and social competencies. Therefore, the formulation of the essence of Trustworthiness, Fairness and Competence according to experts emerged. (3) What are the educational values in QS An-Nisa verse 58 regarding teacher competence. This research used a descriptive-analytical collection technique, namely literature (Study Literature) with a study of interpretations, books, literature, notes, reports related to the subject matter of the research. From this study, it was concluded that educational values according to An-Nisa verse 58 concerning teacher competence. namely, (1) Trustworthy values regarding Teacher Competence, namely the teacher is obliged to have the ability, understanding, management, understanding, development, design, implementation and evaluation and understand competency standards and subject content standards and teaching materials in the curriculum, understand the structure , concepts, and scientific methods that cover teaching materials, understand the relationship between concepts related subjects. As well as applying scientific concepts in everyday life (2) Fair values regarding teacher competencies, namely teachers are obliged to have attitudes and treatments that are applied to their students and provide examples of good behavior in everyday life. Abstrak. Seorang guru profesional harus memiliki beberapa kompetensi yang dibutuhkan seorang guru. Kompetensi adalah bentuk pekerjaan yang bertanggung jawab untuk mencapai suatu tujuan. Kompetensi tersebut meliputi kompetensi Pedagogik, kompetensi Profesional, kompetensi kepribadian, dan kompetensi sosial.. Maka dari itu, munculah rumusan hakikat Amanah, adil dan Kompetensi menurut para ahli. (3) Bagaimana nilai-nilai pendidikan dalam QS An-Nisa ayat 58 tentang kompetensi Guru. Penelitian ini menggunakan metode deskriptif-analitis teknik pengumpulan yaitu kepustakaan (Study Literature) dengan penelahan study terhadap tafsir, buku, literatur, catatan, laporan yang berhubungan dengan pokok masalah penelitian. Dari penelitian ini, disimpulkan bahwa Nilai-nilai pendidikan menurut An-Nisa ayat 58 tentang kompetensi guru. yaitu, (1) Nilai-nilai Amanah tentang Kompetensi Guru yaitu Guru berkewajiban mempunyai kemampuan, pemahaman, pengelolaan, pemahaman, pengembangan, perancangan, pelaksanaan dan evaluasi dan memahami standar kompetensi dan standar isi mata pelajaran serta bahan ajar yang ada dalam kurikulum, memahami struktur, konsep, dan metode keilmuan yang menaungi materi ajar, memahami hubungan konsep antar mata pelajaran terkait. Serta menerapkan konsep-konsep keilmuan dalam kehidupan sehari-hari (2) Nilai-nilai Adil tentang kompetensi Guru yaitu Guru berkewajiban mempunyai sikap dan perlakuan yang diaplikasikan kepada anak didiknya dan memberikan contoh prilaku baik dalam kehidupan sehari-hari.